2015
DOI: 10.1037/a0036771
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention to reduce hazardous drinking and enhance coping among OEF/OIF/OND veterans.

Abstract: Hazardous drinking among US Military combat veterans is an important public health issue. Because recent combat veterans are difficult to engage in specialty mental health and substance abuse care, there is a need for opportunistic interventions administered in settings visited by recent combat veterans such as primary care. This paper describes a brief (single-session) intervention that was recently developed and tested in a sample of veterans of Operations Enduring Freedom, Iraqi Freedom and New Dawn (OEF/OI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…[34] Interventions designed to influence coping styles have been introduced in previous studies and confirmed to be effective among medical students and veterans. [35,36] Therefore, strategies to enhance Chinese physicians’ coping should be developed at the earliest.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Interventions designed to influence coping styles have been introduced in previous studies and confirmed to be effective among medical students and veterans. [35,36] Therefore, strategies to enhance Chinese physicians’ coping should be developed at the earliest.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in rates of PTSD and depression among those who had versus had not experienced a blackout also raises the possibility that individuals with a history of blackout are drinking to cope with these symptoms (McDevitt-Murphy et al, 2015a). Since drinking to cope has also been associated with high-risk drinking among Veterans (Cucciare et al, 2011), future studies may examine the efficacy of coping-specific interventions within this population (McDevitt-Murphy et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Multicomponent interventions with veterans that includes PNF have utilized population-based civilian norms during feedback presentation (Brief, Rubin, Enggasser, Roy, & Keane, 2011; McDevitt-Murphy, Williams, Murphy, Monahan, & Bracken-Minor, 2014). Nonetheless, it is unclear whether PNF reference to civilian norms results in a maximally potent intervention.…”
Section: Appropriateness Of General Population Norms Versus Veteran-smentioning
confidence: 99%